Use of Discussion Methods at History Lessons as Means of Student’s Tolerance Education - Muliar, Oksana; Vasylenko, Nina (Pedagogical Discourse, 2014)
The article investigates the influence of discussion methods of teaching on the process of students’ tolerance formation at the history lessons at the secondary school. The attention is paid to the point that the problem of tolerance education often concerns history, as far as the big amount of questions are contradictory and conflicting. It has been found out that discussion methods are important elements in students’ tolerance formation at the lessons of history. It is determined that the use of discussion methods will assist the formation of such personal traits of students as responsibility, independence, respect and patience towards thoughts and opinions of other people, which are the indicators of tolerance. The resources of discussion methods of teaching are analyzed from the point of view of tolerance education at the history lessons at the secondary school. The authors has chosen such topics of history school course which assist the formation of patience, communicative culture and tolerance as the integral traits of student’s personality.